Keragaman Genetik Dan Rekonstruksi Filogeni Ikan Sidat (Anguilla Spp.) Di Muara Sungai Cimandiri, Pelabuhan Ratu Sukabumi - Edwin Edwin; Reni Mulyani; Neneng Nurbaeti (SANTIKA is a scientific journal of science and technology, 2018)
Indonesian sea waters are the origin of various species of eel (Anguilla spp.) Which are spreadthroughout the world. There are 18 species of eel that have been identified in the world, 9 of whichare in Indonesian waters. The life cycle of eel when larvae and juveniles have morphological formsthat are difficult to distinguish between species. The level of difficulty in identifying eel species willcause delays in disclosure of biodiversity. The high market demand caused concern becausePelabuhan Ratu Bay is one of the southern coast waters of Java Island which has great potential insupplying eel larvae and juveniles. One of the locations where eel fish are caught is the estuary ofthe Cimandiri river located in the southern part of Pelabuhan Ratu bay. Until now, research ongenetic diversity and phylogeny of eel that has entered the estuary of the river has not been donemuch. Even though it is very important to maintain genetic resources, species and ecosystems ofeels. Genetic resources are the basic stages in an effort to protect eel resources in Indonesia,through this method it will facilitate identification even at the species level when compared to justusing identification methods based on morphological characters.This study used eel fish samplesfrom the genus Anguilla taken from the mouth of the Cimandiri River, Pelabuhan Ratu. Sampling iscarried out every month starting from December 2017 - March 2018. Samples are taken using ancoand bubu fishing gear. The sample is then preserved with absolute ethanol solution (96%),followed by the extraction process, PCR (Polymerase Chain Reaction) and electrophoresisamplification. The genus is A. bicolor bicolor, A. nebulosa nebulosa and A. marmorata.